DEVELOPING ESP MATERIALS IN IT AND ECONOMY FIELDS - Kurbanova , Zilola Uralovna; Shamsiyeva , Dilshoda Sadilloyevna (GOLDEN BRAIN, 2024)
English for Specific Purposes (ESP) plays a crucial role in equipping professionals with the language skills necessary to excel in their respective fields. In rapidly evolving sectors like Information Technology (IT) and Economy, developing effective ESP materials is vital for fostering clear communication, understanding complex concepts, and facilitating global collaboration. This article explores key considerations and strategies for creating ESP materials tailored to IT and Economy fields.